Rivals reloaded: adapting to sample-based speed-accuracy trade-offs through competitive pressure - McCaughey, Linda; Ziegler, Johannes; Fiedler, Klaus (Journal of experimental psychology. Learning, memory, and cognition, 2024)
Collecting an adequate amount of information for a decision is an important skill. However, previous experiments on speed-accuracy trade-offs in sample-based decisions revealed marked oversampling that was impervious to various interventions (Fiedler, McCaughey, et al., 2021). When faced with the threat of being preempted by a rival in making decisions, participants seem to reduce information search substantially (Phillips et al., 2014). Such a decrease provides unique opportunities for metareasoning, which should advance people’s understanding of the task and improve their performance. To test this possibility, in the present research (N = 101), participants had to compete with a fast (computer-simulated) rival and indeed substantially reduced self-determined sample size compared to a control condition. This speed increase also carried over to a subsequent decision block without rival, albeit participants regressed to a slower strategy. Mere exposure to a teammate using small samples either in an equivalent competitive version of the task or the standard solitary version led to similar reductions in sample size. This demonstrates that competition is not a necessary requirement for participants to make use of the metareasoning opportunity to improve task performance. Further research is needed to uncover the metacognitive underpinnings of improving performance and facilitate people taking full advantage of such opportunities for metareasoning. (PsycInfo Database Record (c) 2024 APA, all rights reserved)
Gesehen am 12.03.2025